NATURAL KILLER T CELLS IN HEPATIC LEUCOCYTE INFILTRATES IN PATIENTS WITH MALIGNANT PROCESS AND VIRAL HEPATITIS - O. V. Lebedinskaya; I. N. Kabanovskaja; N. K. Akhmatova; E. A. Lebedinskaya; A. V. Lazareva; M. V. Kiselevsky (Медицинская иммунология)
Morphology, topography, and immunohistochemical features of leukocyte infiltrates were studied in various sites of the liver samples from the patients with metastatic disease, been affected by hepatitis B and C viruses at different degree of activity. Liver of СВА mice with implanted САО-1 tumour was also under study. Histochemical, and functional features, as well as immune phenotype of these cells were investigated. It has been shown that the major fraction of leukocyte infiltrates, mostly associated with implanted tumours in experimental mice, and in the areas adjacent to the tumor in humans, like as on the peak of viral hepatitis activity, is composed of lymphocytes. They are presented by large numvers of activated proliferating and differentiating cells bearing specific antigens, as well as natural killers and T-lymphocytes, possessing high-level killer activity towards NK-sensitive, and autologous lines of cancer cells. Hence, the results of our study, generally, confirm the data from literature reporting on existence of a special lymphocyte subpopulation, NKT cells, in human or murine liver affected by hepatitis virus or malignant tumors. The data concerning functional properties of these cells may be used for development of immunotherapy methods of viral diseases and oncological conditions complicated by liver metastases.